Differentiation of monocytes into macrophages in the presence of brucella abortus generates a different phenotype - Bazan Bouyrie, A. J. (2020)
Brucellosis is an infectious disease caused by bacteria of the genus Brucella that triggers a complex host response involving both innate and adaptive immunity. Monocytes and macrophages are not only the first line of defence against Brucella infection but also a main reservoir for the bacteria. Monocytes are recruited in large numbers to sites where the inflammatory process exists and the microenvironment will condition their differentiation to distinct functional profiles of macrophages and dendritic cells. How Brucella could modulate this process remains unclear. The aim of this study was to characterize the phenotype and functions of monocyte-derived macrophages differentiated in the presence of B. abortus. For this, human purified monocytes were cultured with MCSF in presence or absence (control) of heat-killed B. abortus (HKBa) for 5 days. Expression of CD40, HLADR and CD54 was quantified by flow cytometry. Cells showed a lower expression of CD54 and HLADR on monocyte-derived macrophages differentiated in the presence of B. abortus than in control (p<0,05). Moreover, these macrophages were unable to be activated when further stimulated with HKBa or LPS from E. coli, as they were unable to up regulate CD54 or HLADR. Next we analysed the ability of B. abortus to modulate functional aspects of monocyte-derived macrophages. For this, supernatants from macrophages cultures were collected and the secretion of IL-6 and IL-1β was quantified by ELISA. Monocyte-derived macrophages differentiated in the presence of HKBa expressed higher levels of IL-6 and IL-1β than control (p<0,05). Collectively, our results indicate that B. abortus affects the phenotype of monocyte-derived macrophages decreasing HLADR and increasing the secretion of proinflammatory cytokines. This phenotype could affect the activation of T lymphocytes, cooperating with the evasion of immunity by B. abortus.